"They Need to Give Us a Voice":1 Lessons from Listening to Unaccompanied Central American and Mexican Children on Helping Children Like Themselves. (March 2017) - Schmidt, Susan
Children make up half of the world's refugees, yet limited research documents the views of youth about migratory causes and recommendations. While there is wide recognition of migrant children's right to free expression, few opportunities exist to productively exercise that right and provide input about their views. This article analyzes the responses of Central American and Mexican migrant children to one interview question regarding how to help youth like themselves, and identifies several implied "no-win" situations as potential reasons for the migration decisions of unaccompanied children. Furthermore, the children's responses highlight the interconnected nature of economics, security, and education as migratory factors. Examination of children's political speech revealed primarily negative references regarding their home country's government, the president, and the police. The police were singled out more than any other public figures, with particular emphasis on police corruption and ineffectiveness. Additional analysis focused on children's comments regarding migration needs and family. Recommendations for future action include: recognizing entwined motivations and no-win situations that may lead children to leave their countries of origin; promoting integrated approaches to home country economic, security, and education concerns for Central American and Mexican youth; acknowledging migrant children's political interests and concerns; providing youth with meaningful opportunities to contribute their views and suggestions. incorporating migrant children's input and concerns into spending plans for US aid appropriated for Central America; and emphasizing youth leadership development in efforts to address child migration.